INVESTIGATION OF THE INFLUENCE OF THE MODIFIERS P, SR, TI AND COMBINATIONS OF THEM ON THE STRUCTURE AND MECHANICAL PROPERTIES OF ALSI25 ALLOY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The most commonly used elements to modify primary silicon crystals in the structure of hypereutectic aluminum-silicon alloys are phosphorus and sulfur. Phosphorus has been shown to have the highest coefficient of modification with respect to the primary silicon and is therefore a preferred modifier. There are also data on the positive effect of the modifiers Sb, Sr, Ti, and B on the silicon crystals in the structure of this type of alloys. The influence of the modifiers phosphorus, strontium, titanium and combinations of them on the size and shape of both the primary silicon crystals and the silicon crystals in the composition of the eutectic of the AlSi25 alloy has been studied in this work. Mechanical tests have been performed to determine both the strength and the plastic parameters of the investigated alloy (in unmodified and modified state). The classic for this type of alloys modifier - phosphorus - has been introduced into the melt by the ligature CuP10. Strontium has been introduced by the ligature AlSr10, and titanium - by the ligature AlTi5B1, the two ligatures in the form of rods. The investigated alloy has also been modified by combinations of the used modifiers: phosphorus and strontium, phosphorus and titanium.The influence of the used modifiers on the structure and mechanical properties of AlSi25 alloy has been discussed.